Reinstating the Laws of Chance: Breccia’s throw of the dice with Ernesto Sabato’s "Informe sobre ciegos" - Rommens, Aarnoud (2014)
In 1993, the year of his death, Alberto Breccia’s retelling of Ernesto Sabato’s Report on the Blind was finally published (first in Spain by Ediciones B and for the first time in Argentina by Editorial Colihue in 2007). Indeed, finally is the most fitting word to invoke its convoluted publication history: after an agonizing wait lasting over fifteen years – turning out to be a productive incubation period – Sabato eventually granted Breccia permission to recreate and publish the comic version of his literary work. One could say that Breccia’s Report on the Blind is not a single work but is embedded within the dense accumulation of his other visual-verbal experimentations with literary texts, those by H. P. Lovecraft in particular. This article explores the alwayscontroversial relationship between comics and literature and the various aspects of cultural exchange that defy the language of both comics and literary texts. We argue that this exchange turns creates borderline zones that provide new ways to see, read and understand the literary text and its comics adaptation, revealing both their limits and possibilities.